HYDRODYNAMIC PARTICLE TRACKING MODELLING: CASE STUDY OF COASTAL DROWNING AT LEWOLEBA COASTLINE, LEMBATA REGENCY - Filardhi, Azkaa
Activities near and on water bodies are one of the oldest activities throughout human history. Human civilization often begins around water bodies, both rivers and oceans, considering the importance of water in supporting life's needs. Various human activities involve the coast as the basis for the location of their activities, ranging from shipping, fishing, aquaculture, to recreation. These activities are certainly not without risks, considering that waters also pose a threat to the well-being and even the safety of human souls. One of the threats that is the focus of the study is the threat of coastal drowning. The current study focuses on predicting the horizontal location of bodies throughout the duration of the search for drowning victims. The duration of the modeling will be within 15 days from the victim's entry into the body of water. Modeling is carried out by considering current changes in the review waters, including tidal conditions, monsoon winds, and other characteristics that are considered relevant. Taking into account the trend of the movement of the particle model during the search period, it appears that there is a tendency for the bodies to be in the coastal range of Lewoleba Bay. The search on the first day focused on a radius of 2-3 km to the northeast from the entry point, then the search was directed to the coastal area of Lewoleba Bay. On the seventh day until the end of the search period, the focus can be focused on the north side of the Lewoleba Bay coast eastward to the strait between Nereng and Witihama.